P210 VENTRICULAR FIBRILLATION IN AN ELDERLY WOMAN WITH APPARENTLY UNREMARKABLE PAST CARDIOLOGICAL HISTORY: AN UNEXPECTED CULPRIT. (18th May 2022) - Sansonetti, A; Armillotta, M; Amicone, S; Impellizzeri, A; Fabrizio, M; Angeli, F; Bergamaschi, L; Stefanizzi, A; Magnani, I; Rinaldi, A; Foà, A; Galiè, N; et al.
Abstract: An 85–year–old woman experienced cardiac arrest while she was at the supermarket. Cardiopulmonary resuscitation was promptly performed with ROSC after DC shock on ventricular fibrillation and immediate hemodynamic and neurological recovery. The first ECG performed by the rescuers did not show acute ischemic changes and the patient was admitted to the Cardiological Intensive Care Unit. Past medical history revealed only a previous episode of acute pulmonary embolism for which she was on oral anticoagulant therapy for a limited period of time. She had not family history of sudden cardiac death or cardiomyopathies. Before admission she was completely asymptomatic and she never complained of angina pectoris, palpitation or dyspnoea. The echocardiogram at admission showed moderate left atrial enlargement and hypokinesia of left ventricle apex and mid–apical lateral wall with global EF of 50%. Pulmonary and aortic CT angiography showed no pathological findings. In order to rule out an ACS, the patient underwent a coronary angiography which documented the absence of critical coronary stenosis. Finally, a cardiac MRI with gadolinium was performed, revealing the presence of two small areas of transmural LGE affecting inferior basal and lateral mid–apical segments with no edema, consistent with ischaemic myocardial scars. In light of this findings and to rule out paradoxical coronary artery embolism we decided to perform a transcranial echocolordoppler that showed the absence of a patent foramen ovale. Furthermore, continuous ECG monitoring during the hospital stay did not document arrhythmic recurrences. In consideration of the high probability of ischemic heart disease, therapy with antiplatelet agent, beta–blocker, ace–inhibitor and statin was introduced and the patient was discharged after ICD implantation. Three months later, during her first follow–up visit, we documented short episodes of atrial fibrillation at ICD interrogation. This was in line with the hypothesis of a ventricular fibrillation and cardiac arrest in the contest of an ischemic heart disease with myocardial scars probably due to undatale coronary artery embolism. Oral anticoagulant therapy was started in addition to previous therapy.